Analisis Dampak Transformasi Digital Santri Alumni Pondok Pesantren Ngalah terhadap Pengembangan Sustainable Economy di Kecamatan Pasrepan - Mundir, Abdillah; Sulhan, M. Sulhan; Syarwani, Muhammad (CV. Satria Jaya, 2025)
The Eco Digital Transformation Program for Alumni of Pondok Pesantren Ngalah aims to empower pesantren alumni in Pasrepan District, Pasuruan Regency, through the adoption of digital technology in the development of Small and Medium Enterprises (SMEs). The program was implemented through training, workshops, mentoring, and the development of the Eco Digital BOBA application, which is designed to enhance digital skills, business efficiency, and alumni competitiveness. The results indicate significant improvements in the application of digital marketing, e-commerce, and stronger alumni networking collaborations. Beyond technological transformation, this program has also generated positive impacts on local economic growth, community welfare, and environmental sustainability. By adopting a participatory community-based approach, this model is expected to serve as a reference for empowering other pesantren communities to face digital-era challenges while maintaining sustainable economic principles.